2008
DOI: 10.1038/ejhg.2008.221
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins syndrome: etiology, pathogenesis and prevention

Abstract: In association withTreacher Collins syndrome: etiology, pathogenesis and prevention Treacher Collins syndrome (TCS) is a rare congenital disorder of craniofacial development that arises as the result of mutations in the TCOF1 gene, which encodes a nucleolar phosphoprotein known as Treacle. Individuals diagnosed with TCS frequently undergo multiple reconstructive surgeries, which are rarely fully corrective. Identifying potential avenues for rescue and/or repair of TCS depends on a profound appreciation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
192
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(210 citation statements)
references
References 43 publications
(48 reference statements)
6
192
0
7
Order By: Relevance
“…This value was in accordance with the study by Trainor et al, 23 in which 60% of cases were thought to arise as the result of a de novo mutation, based only on family history. However, we were able to confirm a de novo origin of the mutation in only 30/101 (30%) of the apparently sporadic patients.…”
Section: Molecular Datasupporting
confidence: 92%
See 1 more Smart Citation
“…This value was in accordance with the study by Trainor et al, 23 in which 60% of cases were thought to arise as the result of a de novo mutation, based only on family history. However, we were able to confirm a de novo origin of the mutation in only 30/101 (30%) of the apparently sporadic patients.…”
Section: Molecular Datasupporting
confidence: 92%
“…2,23,25 These new data also suggested that the prevalence of carriers of TCOF1 mutations in the population with a very mild phenotype was higher than estimated.…”
Section: Phenotype-genotype Correlationsmentioning
confidence: 75%
“…Grover et al describe unilateral lower lid colobomas exclusively in facial clefting, and all of their patients with bilateral lower lid colobomas had Treacher Collins syndrome (where the colobomas affected the outer third of the lower lids as small notches). Given that lower lid colobomas are reported in 69% of Treacher Collins patients, 22 and that Treacher Collins has an incidence of approximately 1 : 50 000 live births, 22 this group appears to be significantly underrepresented in our case series. This may reflect the fact that the colobomas associated with Treacher Collins are typically small, and may not have been referred for a tertiary opinion.…”
Section: Eyelid Coloboma and Associated Developmental Defectsmentioning
confidence: 76%
“…30 Treacher Collins syndrome (TCS), otherwise known as mandibulofacial dysostosis, is a rare autosomal dominant genetic disorder of the craniofacial and cervicovertebral morphogenesis with a high degree of penetrance and variable phenotypic expression. [31][32][33][34] Affecting the proper formation of the first and second branchial arches, this syndrome occurs during the fifth to eighth weeks of embryonic development with an incidence of 1 in 50,000 live births without gender predilection. 2,[32][33][34] TCS patients have normal intelligence with no associated developmental delay or neurologic disease.…”
mentioning
confidence: 99%
“…[31][32][33][34] Affecting the proper formation of the first and second branchial arches, this syndrome occurs during the fifth to eighth weeks of embryonic development with an incidence of 1 in 50,000 live births without gender predilection. 2,[32][33][34] TCS patients have normal intelligence with no associated developmental delay or neurologic disease. However, as a result of distorted physical appearance, patients often face social challenges and stigma throughout life.…”
mentioning
confidence: 99%